2020
DOI: 10.1136/bmjopen-2020-037637
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes as a smoking cessation aid for patients with cancer: beliefs and behaviours of clinicians in the UK

Abstract: ObjectivesTo explore UK clinicians’ beliefs and behaviours around recommending e-cigarettes as a smoking cessation aid for patients with cancer.DesignCross-sectional online survey.SettingEngland, Wales, Scotland and Northern Ireland.ParticipantsClinicians involved in the care of patients with cancer.Primary and secondary outcomesBehavioural Change Wheel capability, opportunity and motivation to perform a behaviour, knowledge, beliefs, current practice around e-cigarettes and other smoking cessation practices.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It is important for GPs to understand the safety and efficacy of e-cigarettes so effective recommendations can be given to patients if they do wish to use e-cigarettes, or if they are to be recommended or prescribed as a smoking cessation treatment. GPs are stating that they are unsure around the efficacy and safety of e-cigarettes 17,18,[37][38][39][40] however, some findings have revealed that GPs believe e-cigarettes are safer than combustible cigarettes 41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important for GPs to understand the safety and efficacy of e-cigarettes so effective recommendations can be given to patients if they do wish to use e-cigarettes, or if they are to be recommended or prescribed as a smoking cessation treatment. GPs are stating that they are unsure around the efficacy and safety of e-cigarettes 17,18,[37][38][39][40] however, some findings have revealed that GPs believe e-cigarettes are safer than combustible cigarettes 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Current available literature has revealed that GPs seek information and guidance from online government sources and reported that patients were more informed about e-cigarettes than their GPs. 19 , 37 This suggests that there is knowledge deficit around e-cigarettes for smoking cessation, and further research and guidance is needed to provide patients with correct information regarding e-cigarettes as a smoking cessation aid in primary care settings. 16 19 , 37 , 38 , 41 , 43 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent surveys of clinicians [ 37 ] and stop‐smoking practitioners [ 38 , 39 ] have highlighted the need for training in understanding harm reduction. Our study showed that following training, support and the ability to offer e‐cigarettes, clinicians felt comfortable enough to recommend them.…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, several countries such as Belgium and the United Kingdom use ENDS in smoking-cessation treatment. 17,18 However, there is a paucity of data on the association of ENDS with ED. 19 Studies have shown that the nicotine present in combustible cigarettes is responsible for many physiologic changes that contribute to the development of ED.…”
mentioning
confidence: 99%